Financial Flows in the Recycling of Packaging Waste: The Case of France - Pedro Sim\~oes; Nuno Cruz; Rui Cunha Marques (European Regional Science Association (ERSA), 2012)
The recycling of packaging waste is an objective of the Community with very ambitious recycling rate targets laid down in the European law. Research on the operations and on the financial and economic costs that resulted from this environmental policy is an ongoing effort. Currently, there is still no agreement on the `optimal' recycling rates, and on whether the targets should be raised, lowered or preserved. While each member state has currently its own packaging waste management system, there is still a lack of data regarding the actual costs of recycling and on how these costs have been distributed among stakeholders. It is not clear that the packaging and packaging waste Directive is being implemented correctly (i.e. it is not clear that the industry is supporting 100% of the costs of recycling packaging waste). This paper illustrates the French framework and discusses the financial transfers undertaken by Eco-Emballages the entity that manages the Green Dot scheme in this country. For this purpose, we use data from a sample of 45 entities in charge of selective collection and sorting of household packaging waste for the year 2010, covering about 20% of the French population. We match the financial transfers of the Eco-Emballages Group with the costs incurred by the local authorities (which are in charge of selective collection and sorting) and provide a discussion on the rationality and fairness of the system.
Keywords: H11; H21; H23; Q53; Q58; 330; France; green dot; packaging waste; recycling